SDF-Based ILW: Inverse Lax-Wendroff Method with the Signed Distance Function Representation of the Geometric Boundary (Communications in Computational Physics, 2023)
This paper studies the geometric boundary representations for Inverse Lax-Wendroff (ILW) method, aiming to develop a practical computer-aided engineeringmethod without body-fitted meshes. We propose the signed distance function (SDF)representation of the geometric boundary and design an extremely efficient algorithmfor foot point calculation, which is particularly in line with the needs of ILW. Theoretical and numerical analyses demonstrate that the SDF representation of geometricboundary can satisfy ILW’s needs better than others. The effectiveness and robustnessof our proposed method are verified by simulating initial boundary value computational physical problems of Euler equation for compressible fluids.